The developer's dilemma: A survey of structural transformation and inequality dynamics - Armida S. Alisjahbana; Kyunghoon Kim; Kunal Sen; Andrew Sumner; Arief Anshory Yusuf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper discusses the 'developer's dilemma' - a tension emerging from the fact that developing countries are simultaneously seeking structural transformation and broad-based growth to raise incomes of the poor. Simon Kuznets originally hypothesized that structural transformation may have a tendency - in the absence of policy intervention - to put upward pressure on income inequality. However, broad-based economic growth requires steady or even falling income inequality to maximize the growth of incomes at the lower end of the distribution. The purpose of our paper is: (i) to revisit the seminal Kuznets paper in order to understand how Kuznets understood the structural transformation and income inequality relationship precisely; (ii) to discuss the empirical experience of the developing world in terms of structural transformation and, in doing so, to outline a typology of 'varieties' of structural transformation; and (iii) to discuss the structural transformation-inequality relationship and how it may differ under different patterns of structural transformation.
Keywords: D6; L16; 330; income inequality; structural transformation; economic development; Kuznets; Lewis